2016
DOI: 10.1063/1.4939281
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of antimonene grown on Sb2Te3 (111) and Bi2Te3 substrates

Abstract: We explore the formation of single bilayer Sb(111) ultrathin film (Antimonene) on Bi2Te3 and Sb2Te3 substrates for the first time, which is theoretically predicated to be a robust trivial semiconductor but can be tuned to a 2D TI by reducing the buckling height. From angle-resolved photoemission spectroscopy measurements, the antimonene can be well grown on the two surfaces and shows clear band dispersion. The electronic structure of the antimonene shows similar character on the two surfaces, but due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 34 publications
4
78
0
2
Order By: Relevance
“…While both buckled and puckered honeycomb structures are found to be stable [19], buckled arsenene is energetically favored over puckered arsenene [18]. Experimentally the possibility of growing antimonene has been explored on Bi 2 Te 3 and Sb 2 Te 3 substrates [20]. A multilayer arsenene nanoribbon was synthesized on an InAs substrate using a plasma-assisted process [21].…”
Section: Introductionmentioning
confidence: 99%
“…While both buckled and puckered honeycomb structures are found to be stable [19], buckled arsenene is energetically favored over puckered arsenene [18]. Experimentally the possibility of growing antimonene has been explored on Bi 2 Te 3 and Sb 2 Te 3 substrates [20]. A multilayer arsenene nanoribbon was synthesized on an InAs substrate using a plasma-assisted process [21].…”
Section: Introductionmentioning
confidence: 99%
“…According to theoretical calculations, anitmonene presents high carrier mobility11, superior thermal conductivity14, strain induced band transition1015 and promising spintronic properties16. Despite the rapid progress of theoretical works about anitmonene mentioned above, reports of experimental studies on antimonene is still scarce171819. Early this year, Lei et al realized the synthesis of monolayer antimoene on Sb 2 Te 3 and Bi 2 Te 3 by molecular beam epitaxy17.…”
mentioning
confidence: 99%
“…Experimentally, β−antimonene(monolayer of antimony) has been successfully realized on the substrates of 3D topological insulator Bi 2 Te 3 and Sb 2 Te 3 respectively 18 , and the stability of monolayer antimonene allotropes including α−, β−, γ−, and δ−phase were examined by phonon dispersion calculations 17 , which shown that only the monolayer α− and β−antimonene (α/β−Sb) are stable as free-standing monolayers. However, to our knowledge, monolayer arsenene has not been experimentally realized up to now 14 .…”
Section: Introductionmentioning
confidence: 99%